The Impact of a Family History of Alcoholism on the Relationship Between Age at Onset of Alcohol Use and DSM–IV Alcohol Dependence: Results From the National Longitudinal Alcohol Epidemiologic Survey - Grant, Bridget F. (Alcohol Health Res World, 1998)
Both the age at onset of alcohol use and a family history of alcoholism can influence a person’s risk of becoming alcohol dependent. The relationship between lifetime alcohol dependence, age at first alcohol use, and a family history of alcoholism was investigated using data obtained in the 1992 National Longitudinal Alcohol Epidemiologic Survey. This analysis demonstrated that regardless of the family history of alcoholism, respondents with an earlier age of drinking onset were more likely to become alcohol dependent compared with respondents with a later age of drinking onset. Among all age, race, and gender subgroups studied, however, people with a family history of alcoholism had a higher prevalence of lifetime alcohol dependence than did people without such a history.